The influence of carbon nanotubes on the sensitivity of humidity sensors based on organic-inorganic polymer materials - Lysenkov, E.A.; Stryutskiy, O.V.; Gomza, Yu.P.; Klepko, V.V. (Functional Materials, 2015)
The method of sol-gel synthesis of ion-conducting organic-inorganic polymeric nanocomposites modified with carbon nanotubes in amount of 0.1-1.0 wt. %. was developed. The obtained materials were used for fabrication of humidity sensors which were investigated for their sensor properties. It was established that sensor characteristics of the developed materials are significantly dependent on carbon nanotubes content that caused by percolation processes. The optimum characteristics were shown by the material based on organic-inorganic matrix filled with 0.1 % carbon nanotubes.